background image

Proof

a ζ

Q

(

U

;

τ

)

(

)

K

b

iff

a

and

b

are in the same connected component

regarding

Q

((

U

;

τ

)

|

K

).

Let’s prove that

a ζ

Q

(

U

;

τ

)

(

)

K

b

=

a ζ

Q

(

U

;

τ

)

(

)

K

b

.

We need to prove that

a ζ

Q

(

U

;

τ

)

(

)

K

b

iff

a

and

b

are in the same connected

component regarding

Q

((

U

;

τ

)

|

K

). (Then also

a ζ

Q

(

U

;

τ

)

(

)

K

b

iff

a

and

b

are

in the same connected component regarding

Q

((

U

;

τ

)

|

K

).) If

a

and

b

are in the

same connected component then

x

(

Q

(

U

;

τ

))

|

K

y

that is

a ζ

Q

(

U

;

τ

)

(

)

K

b

. Let

now

a ζ

Q

(

U

;

τ

)

(

)

K

b

. Suppose

a

X

and

b

Y

where

X

and

Y

are distinct

connected components regarding

Q

((

U

;

τ

)

|

K

). Then

b

U

\

X

,

X

(

U

\

X

) =

U

and

X

(

U

\

X

) =

. Thus

X Q

((

U

;

τ

)

|

K

) (

U

\

X

) that is for some

x

X

and

y

U

\

X

we have

x τ

K

y

what is impossible because

x

and

y

lie in different

connected components.

ζ

Q

(

U

;

τ

)

(

)

K

= (

≡ |

(

U

;

r

)

|

K

);

a

≡ |

Q

(

U

;

τ

)

|

K

b

a L

(CC(

Q

(

U

;

τ

)))

K

b

a L

(CC(

T

(

U

;

τ

)))

K

b

a

|

T

(

U

;

τ

)

|

K

b

(used the theorem 2).

L

(CC(

Q

(

U

;

τ

)))

K

=

ρ

(

P

K

CC(

Q

(

U

;

τ

))) =

ρ

(CC((

Q

(

U

;

τ

))

|

K

)) =

ρ

(CC(

Q

((

U

;

τ

)

|

K

))) =

ρ

(LC((

U

;

τ

)

|

K

)). So if

a

≡ |

Q

(

U

;

τ

)

|

K

b

then

a

and

b

lie in the same connected

component regarding (

U

;

τ

)

|

K

. Thus

a τ

K

b

.

Let now

a τ

K

b

. Suppose that

a

and

b

lie in different connected components

regarding (

U

;

τ

)

|

K

. Then by equivalence every points of these components are

linked and thus they are one connected component. By contradiction

a

and

b

lie in the same connected component regarding (

U

;

τ

)

|

K

.

So we proved

a

≡ |

Q

(

U

;

τ

)

|

K

b

a τ

K

b

.

5.4. Relationships of

Q

(

U

;

τ

)

and

T

(

U

;

τ

)

Let find a formula which allows to find

T

(

U

;

τ

) knowing

Q

(

U

;

τ

) (to the

extent of equal normalization).

Let (

U

;

r

) is a connector space.

Definition 25

I will define the connector space

β

(

U

;

r

) = (

U

;

r

)

by the formula

(for every

A, B

P

U

)

A r

B

A

B

CC(

r

)

.

Lemma 4

Let

X

,

Y

,

A

,

B

are sets. If

X, Y, A, B

6

=

and

X

Y

=

A

B

then

X

A

6

=

∅ ∧

Y

B

6

=

or

X

B

6

=

∅ ∧

Y

A

6

=

.

Proof

If

a

X

then

a

A

or

a

B

. Let for example

a

A

. Thus

X

A

6

=

.

If

Y

B

=

then

B

X

and

Y

A

, so having

X

B

6

=

∅ ∧

Y

A

6

=

.

Theorem 16

N

(

T

(

U

;

τ

)) =

N

(

β

(

Q

(

U

;

τ

)))

for every increasing equivalence

link space

(

U

;

τ

)

.

19